The Inner Boundaries of German Literature and the Poetical Exterritorialization of "Others" - Joachimsthaler (UNI-MARBURG), Jürgen (ANTARES: Letras e Humanidades, 2016)
As with any other literature, German literature is spread over a territory, in which the language of this literature (German) is not the only language to be spoken and written. In the 18th century, Sorbs, Lithuanians, Danes, Polish, and French lived there. In the 19th century, the growing migration added new groups. Peoples were mingled; the migration through German territories was accompanied by a wandering of signs through German cultural spheres. German authors targeting the national book market had to deal with this as a part of daily life. Many writers tried to mark cross-cultural influences as foreign and not belonging to what they understood as “German”; they developed techniques to extraterritorialize “others” in their narrative worlds. These “others” were integrated as foreigners, whose strangeness thus formed the inner core of German identity.